Preparing to Understand and Use Science in the Real World: Interdisciplinary Study Concentrations at the Technical University of Darmstadt. - Liebert, Wolfgang J. (Science & Engineering Ethics, 2013)
In order to raise awareness of the ambiguous nature of scientific-technological progress, and of the challenging problems it raises, problems which are not easily addressed by courses in a single discipline and cannot be projected onto disciplinary curricula, Technical University of Darmstadt has established three interdisciplinary study concentrations: “Technology and International Development”, “Environmental Sciences”, and “Sustainable Shaping of Technology and Science”. These three programmes seek to overcome the limitations of strictly disciplinary research and teaching by developing an integrated, problem-oriented approach. For example, one course considers fundamental nuclear dilemmas and uses role-playing techniques to address a controversy in the area of nuclear security. At the same time, incorporating interdisciplinary teaching into a university that is organized around mono- or multi-disciplinary faculties also poses a number of challenges. Recognition in disciplinary curricula, and appropriate organizational support and funding are examples of those challenges. It is expected that science and engineering students, empowered by such interdisciplinary study programmes, will be better prepared to act responsibly with regard to scientific and technological challenges.